Antioxidant Activity Test of Ethanol Extract from The Leaves and Bark of Kapur (Dryobalanops aromatica) from Distillation Solid Waste Using the DPPH and ABTS Methods - Sari, Nur Maulida; Zarta, Abdul Rasyid; Salusu, Heriad Daud; Hernandi, Muhammad Fikri; Ramadhan, Mohammad Ridho; Pragaloka, Nur Indah; Kerawing, Rosalinda; Muis, Puspitasari; Raihanah, Siti; Jasmawati, Jasmawati; Aryani, Farida (Biology, Medicine, & Natural Product Chemistry, 2025)
One of the endemic plants of East Kalimantan, kapur (Dryobalanops aromatica) belongs to the Dipterocarpaceae family and is typically used by the locals for essential oils. Solid waste is only used as a natural fertilizer, while the leaves and bark of Kapur (Dryobalanops aromatica) are often only used for the essential oil extracted. Research on solid waste from distilling kapur (Dryobalanops aromatica) has never been done. This investigation aimed to find the possible concentration of secondary metabolite chemicals and antioxidants in the ethanol extract of solid waste from distilling Kapur leaves and bark (Dryobalanops aromatica). The ethanol extract of Kapur leaves and bark (Dryobalanops aromatica) will undergo phytochemical testing utilizing a qualitative test method to ascertain the presence of secondary metabolite chemicals. The ethanol extract of Kapur leaves and bark (Dryobalanops aromatica) will be tested for antioxidant activity against DPPH and ABTS free radicals using a UV Spectrophotometer. The results of the phytochemical analysis showed that the ethanol extracts from the leaves and bark contained alkaloids, flavonoids and tannin. Triterpenoids are only found in the bark extracts, while saponins and steroids are only found in the leaves extracts. Antioxidant activity of Dryobalanops atomatica extract showed that ethanol extract displayed an ability to inhibit DPPH free radical in both the leaves and bark ethanol extracts, with percentages of 83.24% and 94.91% at 25 ppm concentration, respectively. Antioxidant activity of Dryobalanops atomatica extract showed that ethanol extract could inhibit DPPH free radical in the leaves and bark ethanol extracts, with percentages of 83.24% and 94.91% at 25 ppm concentration, respectively. Antioxidant activity of Dryobalanops atomatica extract showed that ethanol extract display an ability to inhibit ABTS free radical with a percentage of 84.23% at 50 ppm concentration in the leaves extracts, followed by 82.62% percentage of inhibition at 100 ppm concentration. According to the findings of the study, post-distillation solid waste from Dryobalanops aromatica leaves and bark had the potential to develop as a natural antioxidant.